Precipitation inﬂuence assessment on accidents risk outside built-up areas - E. V. Pechatnova; K. E. Safronov (Вестник СибАДИ)
Introduction. The Road Traﬃc Safety Strategy in the Russian Federation for 2018-2023 includes the tasks of reducing an accident rate, among which the problem of accidents outside built-up areas is highlighted. The accidents outside built-up areas are characterized with high severity of consequences. The analysis of accident factors is necessary for the development of methods to improve road safety by preventing road accidents.Determining functional dependence is necessary for the development of information road safety management systems.The article is devoted to the study of the inﬂuence of precipitation amount on the change in the risk of road accidents.Materials and methods. The study applied a relative risk analysis, which is calculated by comparing observed variables of two groups: total rainfall data (climatic frequencies) and accident sampling (frequency at time of accident).The study bases on the data of road accidents with victims and material damage that have been registered on the А-322 road (Barnaul – Rubtsovsk – the state border with the Republic of Kazakhstan) during the period from 2012 to 2017.Results. A graph functional dependence and piece wise linear functional dependency were obtained. As the result of approximation, functional dependencies in the form of third-order polynomial function were found.Practical importance. The obtained functional dependencies can be used in the management system to assess the current risk of road accidents on roads outside build-up areas. The regularity of the inﬂuence of precipitation on the risk of road accidents can be used to implement accident prevention measures at the stage of road design and operation.Originality. The study contains new results on the nonlinear form of the functional dependence of the amount of precipitation on the risk of road accidents.